2019
DOI: 10.1002/pmic.201800394
|View full text |Cite
|
Sign up to set email alerts
|

The Proteome of Pancreatic Cancer‐Derived Exosomes Reveals Signatures Rich in Key Signaling Pathways

Abstract: Exosomes are membrane‐bound vesicles that traffic small molecular cargos. These cargos participate in cell–cell communication and contribute to the pathogenesis of many disease including cancer. How these mechanisms contribute to communication within the pancreatic adenocarcinoma (PDAC) microenvironment and how they contribute to PDAC biology are poorly understood. Performed in this study are comprehensive, quantitative comparisons of the proteomes of three PDAC cell lines to those of the exosomes they produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…We analyzed by western blotting the extracellular expression level of vimentin (VIM) in CM-mock, CM-R273H, and CM-R175H of AsPC-1 cells, confirming the hyper-secretion of VIM induced by both mutant p53 isoforms in order to validate mass spectrometry data ( Figure S3 ). We have further investigated whether these 15 proteins were already identified in PDAC-derived exosomes and seven of them, namely PROCR, TIMP1, EZR, PSAP, VIM, CLSTN1 and CFL1, were detected in the proteome of pancreatic cancer exosomes using mass spectrometry [ 38 ], which suggests their roles as key signaling molecules.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed by western blotting the extracellular expression level of vimentin (VIM) in CM-mock, CM-R273H, and CM-R175H of AsPC-1 cells, confirming the hyper-secretion of VIM induced by both mutant p53 isoforms in order to validate mass spectrometry data ( Figure S3 ). We have further investigated whether these 15 proteins were already identified in PDAC-derived exosomes and seven of them, namely PROCR, TIMP1, EZR, PSAP, VIM, CLSTN1 and CFL1, were detected in the proteome of pancreatic cancer exosomes using mass spectrometry [ 38 ], which suggests their roles as key signaling molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Exosomes transport a distinct molecular cargo of proteins and nucleic acids (mRNA, miRNA and genomic dNA) in peripheral blood (PB) and other bio-fluids (e.g., urine and saliva), and are recognized as relevant for the diagnosis and prognosis of certain pathologies, particularly solid tumors. Several studies have demonstrated that the proteins and nucleic acids contained within the exosomes of cancer patients can be isolated and identified as exosomal markers associated with cancer evolution (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional differential ultracentrifugation has been widely used, but may not be able to remove all contaminants [1,2]. To obtain sEVs with small size, 0.22 μm filtration membranes were used in some studies to remove the microvesicles [3,4], but the filtration membrane could not remove protein contaminants, which may mislead the study results [5,6]. The International Society for Extracellular Vesicles (ISEV) advised that the qualities of EV from different isolation methods were different [7].…”
Section: Introductionmentioning
confidence: 99%